KEPEMIMPINAN PERUBAHAN DALAM PENINGKATAN MUTU PENDIDIKAN (STUDI KASUS DI MADRASAH TSANAWIYAH NEGERI 3 PAMEKASAN) - El-Kafi, Ach. Habibi (CV. Jendela Gagasan, 2024)
This research seeks to understand efforts to change in its main education in small complexes, namely in madrasas. In the future the direction of change is getting faster, if left alone without steps and preparation to change the change is an opportunity, then what will happen is a threat to the delivery of the madrasa. Strong, intelligent, visionary leadership and development oriented will design and manage everything to go to change in the organization led. If so, the desired change will be achieved optimally and according to expectations. Leadership strength in this change is in terms of personality and commitment. Because facing all the changes in a leader needing power, confidence, confidence, and extra self involvement to change the threat to opportunities. The purpose of this study focused on three things, namely; 1) What form the leadership of the Chief of the Madrasah Chief at MTsN 3 Pamekasan, 2) How the steps of the madrasa in making changes in MTsN 3 Pamekasan, 3) how the obstacles and solutions in making changes in MTsN 3 Pamekasan. This study uses a qualitative approach with a case study type. This research was conducted at Madrasah Tsanawiyah Negeri 3 Pamekasan. Data collection using interview techniques, observation, documentation. Data analysis was carried out by data condensation stages, data presentation and drawing conclusions. Check the validity of data through increasing perseverance and source triangulation. The results of this study; 1. Form of change by the head of the madrasa. (a) Change Mindset and Psycology HR covers, teachers, educational staff, students and the community (b) Institutional Changes include, Office Management, Curriculum Management and Public Relations Management (C) Change of Achievement. 2. Madrasah head steps in making changes, a) Research, B) Analysis, C) Socialization, D) Trying to make changes, and e) accept change. 3. Obstacles and solutions in making changes, a) Teacher and student resistance, the solution is given a seminar program, workshop, training, tausiyah and permissions. b) Community resistance, the solution is held by the Association of Guardian Program. c) Minimal funds, the solution to the development of madrasah cooperatives.